Responding To Drama: The Efl Students’ Reader-Response Literary Analysis - Febriani, R Bunga; Rohayati, Dedeh; Syafryadin, Syafryadin (Universitas Galuh, 2024)
This article presents the EFL students' reader-response literary analysis of an English drama. The study aims to investigate the EFL students' engagement in reading drama as one of the literary genres and the way they make a Reader-Response literary analysis of the drama. The writer carried out the present research by analyzing the students' reflective essays in which they respond to an English drama entitled